2020
DOI: 10.3390/s20247190
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Active Noise Control System for the Attenuation of Road Noise Inside a Vehicle Cabin

Abstract: This paper proposed a local active control method for the reduction of road noise inside a vehicle cabin. A multichannel simplified hybrid active noise control (sHANC) system was first developed and applied to the rear left seat of a large sport utility vehicle (SUV). The attenuation capability of the sHANC system was investigated through simulations, using reference signals provided by accelerometers on the suspensions and bodywork of the vehicle and microphones on the floor of cabin, respectively. It was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, although sales of ultracompact EVs began in around 2020, no noticeable growth in demand has been observed thus far. One of the reasons for this is the decrease in comfort owing to noise inside the vehicle while driving [1][2][3]. While ultracompact EVs are compact and lightweight, the rigidity of the outer plate is low.…”
Section: Introductionmentioning
confidence: 99%
“…However, although sales of ultracompact EVs began in around 2020, no noticeable growth in demand has been observed thus far. One of the reasons for this is the decrease in comfort owing to noise inside the vehicle while driving [1][2][3]. While ultracompact EVs are compact and lightweight, the rigidity of the outer plate is low.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang proposed a normalized frequency-domain block FxLMS (NFB-FxLMS) to reduce the interior noise of vehicles and showed that the higher the vehicle speed, the more obvious the advantages of the NFB-FxLMS [4]. Jia proposed a modified hybrid ANC algorithm combining the vibrational and acoustical signals for the reduction of road noise inside a vehicle cabin and achieved a 3.7 dBA overall noise reduction [5]. Reddy presented the application of filtered-x recursive least-squares (FxRLS), filtered-x affine projection algorithm (FxAPA) and FxLMS on an fMRI bore test-bed [6] and developed a new hybrid adaptive algorithm to balance the convergence and steady-state error based on the combination of FxRLS and FxNLMS [7].…”
Section: Introductionmentioning
confidence: 99%
“…The output of these secondary sound sources is arranged so as to destructively interfere with the acoustic noise from the primary source. The basic idea behind ANC systems has been reported for the last decades [11][12][13][14], and it still is a research field with continuous dissemination of interesting results [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%